2013
DOI: 10.1007/s00280-013-2146-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between cetuximab therapy and corrected QT interval changes in patients with advanced malignancies from solid tumors

Abstract: These results suggest that cetuximab can be safely administered as a single agent without risk of effect on QTc interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
1
8
1
Order By: Relevance
“…Consistent with the literature regarding cetuximab administration for therapeutic purposes, a small increase of QTc interval was seen after infusion of the loading dose cetuximab with no further increase after cetuximab-IRDye800. 19,20 QTc interval gradually decreased to baseline and none of the patients had persistent increased QTc after the observation period.…”
Section: Resultsmentioning
confidence: 93%
“…Consistent with the literature regarding cetuximab administration for therapeutic purposes, a small increase of QTc interval was seen after infusion of the loading dose cetuximab with no further increase after cetuximab-IRDye800. 19,20 QTc interval gradually decreased to baseline and none of the patients had persistent increased QTc after the observation period.…”
Section: Resultsmentioning
confidence: 93%
“…In the dosages ranging from 7.5 to 75 mg/kg in rhesus monkeys studies, Erbitux injection did not cause severe side-effects 7,8 . As reported by researches on Erbitux or its biosimilars, they reported that Erbitux did not cause vital organs pathological alterations, except rarely reported heart associated heart failure and increased heart beating rate 9 .…”
Section: ■ Discussionmentioning
confidence: 85%
“…Through the adverse event reporting, the clinical trials did not manage to establish a relationship between the two. The only prospective clinical study [ 60 ] identified in the literature with this primary objective was performed in 20 centers in USA, on 51 patients treated with Cetuximab for advanced H&N, NSCLC, CRC and other cancers, treated with Cetuximab monotherapy. Serial ECG monitoring was performed and also dosing of seric Cetuximab concentration; from all patients, 37 were included in the final analyses.…”
Section: Cardiovascular (Cv) Side Effects Of Cetuximabmentioning
confidence: 99%